Annie Pederson: Edge of Dusk - Book 1 - Coble, Colleen (Nashville, Tennessee : Thomas Nelson, 2022)
"USA TODAY bestselling romantic suspense author Colleen Coble launches a brand-new series set in the fan-favorite Upper Peninsula that incorporates beloved characters from her Rock Harbor series"--
Keywords: Widows -- Fiction; Murder -- Fiction. -- Investigation; Bereavement -- Fiction; Upper Peninsula (Mich) -- Fiction; Christian fiction; Detective and mystery fiction